PENDIDIKAN KESEHATAN ANTENATAL CARE (ANC) DI DUSUN TRUKAN DESA SEGOROYOSO KECAMATAN PLERET KABUPATEN BANTUL - Viantika Kusumasari; Fitri Dian Kurniati (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The irregular antenatal care (ANC) visit during pregnancy can cause problems on pregnancy, childbirth, puerperal, lactation, and infant mortality. The ANC examination in Bantul for pregnant women K4 in 2005 was below target. In Trukan, there were several pregnant women who did not do routine ANC visit, faced problems during pregnancy, and low birth weight infants. People have not received health education about ANC. The target of the output of community service activities is to improve knowledge pregnant women and women in their reproductive age about ANC and publication to national journals. Method used was health education by mass lecturing and discussion using power point and leaflets. Community service is carried out in Trukan, Segoroyoso, Pleret, Bantul in November 2019 in one meeting. The target were 40 pregnant women and women in their reproductive age. There were pre-test and post-test on ANC to find the knowledge level of the participants. The conducted health education is able to improve the average value of knowledge about ANC of pregnant women and women in their reproductive age in Trukan is 16 point. The knowledge level of pregnant women and women in their reproductive age does not entirely affect the regularity of ANC visit.